2019
DOI: 10.1093/zoolinnean/zlz069
|View full text |Cite
|
Sign up to set email alerts
|

Tissue preservation can affect geometric morphometric analyses: a case study using fish body shape

Abstract: In geometric morphometrics, the extent of variation attributable to non-biological causes (i.e. measurement error) is sometimes overlooked. The effects of this variation on downstream statistical analyses are also largely unknown. In particular, it is unclear whether specimen preservation induces substantial variation in shape and whether such variation affects downstream statistical inference. Using a combination of empirical fish body shape data and realistic simulations, we show that preservation introduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Finally, when there is a doubt on repeatability and when datasets do not overlap between users, it is also possible to remove the effect of the origin of the data by introducing this as a factor in the analysis (e.g. [ 16 ]) but this requires the critical assumption that the variation of the hypothetical bias is not in the same direction as the biological variation explored. This can however be done in trying to keep balanced data among data providers for avoiding violating “the marginality principle” in linear modeling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, when there is a doubt on repeatability and when datasets do not overlap between users, it is also possible to remove the effect of the origin of the data by introducing this as a factor in the analysis (e.g. [ 16 ]) but this requires the critical assumption that the variation of the hypothetical bias is not in the same direction as the biological variation explored. This can however be done in trying to keep balanced data among data providers for avoiding violating “the marginality principle” in linear modeling.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have evidenced small variation between multiple operators when compared with the targeted biological signal (e.g. [ 16 ]) others have demonstrated that IO bias can lead to substantial variation on geometric morphometric analyses (e.g. [ 17 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantification of presentation and projection error requires replication which generally must be conducted at specimen housing facilities, and is seldom assessed in the literature (but see Fruciano, ; Fruciano et al, ; Robinson & Terhune, ) though their potential for obscuring biologically meaningful shape variation is considerable (Fruciano, ; Zelditch et al, ). Few studies demonstrate how several of these error types can combine to impact statistical result‐based inferences (but see Fruciano et al, ,; Robinson & Terhune, ; Vergara‐Solana, García‐Rodríguez, & Cruz‐Agüero, ). This context is important because ecological, archeological, and paleontological studies often use statistical grouping analyses (e.g., linear discriminant analysis (LDA)/canonical variate analysis) to determine the taxonomic or ecological affinity of unknown specimens (Kovarovic, Aiello, Cardini, & Lockwood, ; Webster & Sheets, ).…”
Section: Introductionmentioning
confidence: 99%